Political activity of the Algerian People's Party in Zeban (1937-1954) - fraih, lekhmissi (The Algerian Historical Journal, 2026)
Political resistance, as a manifestation of the Algerian national movement since the beginning of the twentieth century, has been the subject of many historical studies, which also knew a development in the orientation towards local studies, with the aim of reaching the historical facts that Algerians lived in every region or city of Algeria during the period of the French occupation. . From this standpoint, this study came to shed light on the political activity of the Algerian People's Party in the Zeban region since its inception in 1937, through the resort of its militants to secrecy after its dissolution in 1939, then its activity within the framework of the "Movement for the People of the Statement and Freedom" (1944-1945), and in demonstrations May 8, 1945, and the period that followed it, and after it appeared again into the open as the "Movement for the Triumph of Democratic Freedoms" until the outbreak of the Liberation Revulation 1954.